Resolving Ethical Dilemmas in a Tertiary Care Veterinary Specialty Hospital: Adaptation of the Human Clinical Consultation Committee Model. Issue 2 (1st February 2018) - Rosoff, Philip M.; Moga, Jeannine; Keene, Bruce; Adin, Christopher; Fogle, Callie; Ruderman, Rachel; Hopkinso, Heather; Weyhrauch, Charity
Abstract : Technological advances in veterinary medicine have produced considerable progress in the diagnosis and treatment of numerous diseases in animals. At the same time, veterinarians, veterinary technicians, and owners of animals face increasingly complex situations that raise questions about goals of care and correct or reasonable courses of action. These dilemmas are frequently controversial and can generate conflicts between clients and health care providers. In many ways they resemble the ethical challenges confronted by human medicine and that spawned the creation of clinical ethics committees as a mechanism to analyze, discuss, and resolve disagreements. The staff of the North Carolina State University Veterinary Hospital, a specialty academic teaching institution, wanted to investigate whether similar success could be achieved in the tertiary care veterinary setting. We discuss the background and rationale for this method, as well as the approach that was taken to create a clinical ethics committee.